Impact of flow disruptions in the delivery room. (May 2020) - Herrick, Heidi M.; Lorch, Scott; Hsu, Jesse Y.; Catchpole, Kenneth; Foglia, Elizabeth E.
Abstract: Aim: Flow disruptions (FDs) are deviations from the progression of care that compromise safety and efficiency of a specific process. The study aim was to identify the impact of FDs during neonatal resuscitation and determine their association with key process and outcome measures. Methods: Prospective observational study of video recorded delivery room resuscitations of neonates <32 weeks gestational age. FDs were classified using an adaptation of Wiegmann's FD tool. The primary outcome was target oxygenation saturation achievement at 5 min. Secondary outcomes included achieving target saturation at 10 min, time to positive pressure ventilation for initially apnoeic/bradycardic neonates, time to electrocardiogram signal, time to pulse oximetry signal, and time to stable airway. Multivariable logistic regression assessed association between FDs and achieving target saturations adjusting for gestational age and leader. Associations between FDs and time to event outcomes were assessed using Cox proportional hazards models. Results: Between 10/2017–7/2018, 32 videos were included. A mean of 52.6 FDs (standard deviation 17.9) occurred per resuscitation. Extraneous FDs were the most common FDs. FDs were associated with an adjusted odds ratio of 0.92 (95% confidence interval [CI] 0.80–1.05) of achieving target saturation at 5 min and 0.94 (95% CI 0.84–1.05) at 10 min. There was no significant evidence to show FDs were associated with time to event outcomes. Conclusions: FDs occurred frequently during neonatal resuscitation. Measuring FDs is a feasible method to assess the impact of human factors in the delivery room and identify modifiable factors and practices to improve patient care.